2014
DOI: 10.1021/bm500899r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Activity of an Immobilized Antimicrobial Peptide Containing Bactericidal PEG-Hydrogel

Abstract: A single step immobilization-polymerization strategy of a highly active antimicrobial peptide into a soft hydrogel network on a poly(ethylene terephthalate) surface using thiol-ene chemistry is described. The bactericidal hydrogel was molecularly characterized via Coomassie and Lowry assay protein staining agents as well as by X-ray photoelectron spectroscopy. The bactericidal activity was established against Staphylococcus aureus and Staphylococcus epidermidis, two bacterial strains commonly associated with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…237,238 A Gram-positive antibacterial activity possessing peptide (KIGAKI)3-NH2 with hairpin and self-assembly structure was incorporated with hydrogels by Liu et al 239 Highly active AMP CKRWWKWIRW-NH2 was immobilized to the surface of poly(ethylene terephthalate) hydrogel, thus establishing bactericidal activity against S. aureus and S. epidermidis. 240 Poly-lysine, a popular AMP that has been reported by Zhou et al, was applied in photopolymerized antimicrobial hydrogels, which can be promising coatings for medical devices and implants (Figure 7). 241,242 In the research studies conducted by Jiang et al, 243 cationic multidomain peptides (MDPs) demonstrated a better antimicrobial activity in hydrogels than in solution.…”
Section: Antimicrobial Polypeptidesmentioning
confidence: 99%
“…237,238 A Gram-positive antibacterial activity possessing peptide (KIGAKI)3-NH2 with hairpin and self-assembly structure was incorporated with hydrogels by Liu et al 239 Highly active AMP CKRWWKWIRW-NH2 was immobilized to the surface of poly(ethylene terephthalate) hydrogel, thus establishing bactericidal activity against S. aureus and S. epidermidis. 240 Poly-lysine, a popular AMP that has been reported by Zhou et al, was applied in photopolymerized antimicrobial hydrogels, which can be promising coatings for medical devices and implants (Figure 7). 241,242 In the research studies conducted by Jiang et al, 243 cationic multidomain peptides (MDPs) demonstrated a better antimicrobial activity in hydrogels than in solution.…”
Section: Antimicrobial Polypeptidesmentioning
confidence: 99%
“…DX-nisin lm. Since nisin was not released from DX-nisin lm, the activity of (DX-nisin) 60 lm against S. epidermidis was examined using modied Japanese Industrial Standard test JIS Z 2801:2000 35,36 for surface antibacterial efficacy. Fresh overnight grown 10 9 CFU mL À1 bacterial suspension in LB medium was diluted with PBS to obtain 10 5 CFU mL À1 .…”
Section: Antimicrobial Activity Of the Lbl Lmsmentioning
confidence: 99%
“…Displaying multiple modes of intracellular and extracellular action, antimicrobial peptides demonstrate a reduced propensity for developing antimicrobial resistance and are a significant prospect for solving the current shortage of antimicrobials in pharmaceutical development [13]. Several research groups have studied their incorporation into synthetic hydrogel matrices for the prevention of biomaterial and wound infections with promising results thus far [14,15,16]. Hydrogels possessing inherent antimicrobial properties represent a significant benefit by reducing microbial contamination within the matrix and at the wound/implantation site [17].…”
Section: Introductionmentioning
confidence: 99%